Atezolizumab-induced vanishing bile duct syndrome: a case report - Noblejas Quiles, Carlos Tomás; Macías Cerrolaza, José Antonio; Benitez Fuentes, Javier David; López Gómez, Laura; Sánchez Cánovas, Manuel; Nevado Rodríguez, María; Martín Cascón, Miguel; Vigueras Campuzano, Isabel; Chaves Benito, Asunción; Lázaro Sánchez, Antonio David (Frontiers in Oncology, 2025)
Vanishing bile duct syndrome (VBDS) is a rare but potentially fatal cause of intrahepatic cholestasis, usually associated with autoimmune, infectious or drug-induced etiologies. We present the first documented case of VBDS induced by Atezolizumab, an immune checkpoint inhibitor approved as adjuvant therapy in resected stage II-IIIA non-small cell lung cancer. A 63-year-old man developed cholestatic liver injury after three cycles of Atezolizumab, with progressive jaundice and elevated bilirubin despite immunosuppressive therapy. The diagnosis was confirmed by liver biopsy, which revealed intrahepatic bile duct leakage in more than 50% of the portal tracts. Despite initial stabilization, the patient’s bilirubin levels continued to rise and liver transplantation was contraindicated. He was discharged with immunosuppressive and supportive treatment, under close follow-up. This case highlights the need for greater clinical awareness of rare immunotherapy-associated immune-mediated hepatotoxicities, and underlines the importance of histological confirmation in severe or atypical presentations.